2009
DOI: 10.3852/08-199
|View full text |Cite
|
Sign up to set email alerts
|

DNA phylogeny reveals polyphyly ofPhomasectionPeyronellaeaand multiple taxonomic novelties

Abstract: Species of the anamorph genus Phoma are commonly isolated from a wide range of ecological niches. They are notoriously difficult to identify due to the paucity of morphological features and the plasticity of these when cultivated on agar media. Species linked to Phoma section Peyronellaea are typified by the production of dictyochlamydospores and thus have additional characters to use in taxon delineation. However, the taxonomy of this section is still not fully understood. Furthermore the production of such c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(136 citation statements)
references
References 18 publications
5
129
0
2
Order By: Relevance
“…Using GenBank to identify some genera to species level must be treated with caution unless the sequence is derived from an extype strain (Cai et al 2011a,b;Ko Ko et al 2011;Maharachchikumbura et al 2011, Manamgoda et al 2011Tempesta et al 2011;Udayanga et al 2011;Wikee et al 2011;Yang et al 2011). We adopted a 99 % sequence BLAST similarity threshold to determine species names (Gazis et al 2011) because recent studies used more variable gene regions than the ITS to delimitate species that were frequent in our sampling (Aveskamp et al 2009;Aveskamp et al 2010;Chaverri et al 2011;Schubert et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Using GenBank to identify some genera to species level must be treated with caution unless the sequence is derived from an extype strain (Cai et al 2011a,b;Ko Ko et al 2011;Maharachchikumbura et al 2011, Manamgoda et al 2011Tempesta et al 2011;Udayanga et al 2011;Wikee et al 2011;Yang et al 2011). We adopted a 99 % sequence BLAST similarity threshold to determine species names (Gazis et al 2011) because recent studies used more variable gene regions than the ITS to delimitate species that were frequent in our sampling (Aveskamp et al 2009;Aveskamp et al 2010;Chaverri et al 2011;Schubert et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The 2012 roots collected from the field on different weeks had significantly (P < 0.0001) different levels of weight loss measured after 148 (week 1 roots) to 120 (week 5 roots) days in storage; therefore, the data were analyzed separately by week. The overall fungicide treatment means for root weight loss by week were 10,8,8,4, and 5% for roots collected in weeks 1 through 5, respectively. The fungicide-field interaction term was not significant for weeks 1 (P = 0.1932), 2 (P = 0.2679), 3 (P = 0.6879), 4 (P = 0.2258), and 5 (P = 0.2060).…”
Section: Resultsmentioning
confidence: 99%
“…Because not all the DNA regions were informative for differentiating all the fungal species observed, the DNA regions sequenced for each mycelial type were chosen based on previous phylogenetic analyses from taxonomic studies for the fungal genera observed (i.e., Athelia-like, Botrytis, Fusarium, Mucor, Neonectria, Penicillium, Phoma, Rhizopus, Sarocladium, and Talaromyces spp. ; [3][4][5]18,20,21,25,35,39,43,53,55,59,63). The isolates were each grown in potato dextrose broth (PDB; Becton Dickinson & Co.) on a DS-500E orbital shaker (VWR International, LLC, Aurora, CO; 100 rpm) at 21°C until a ball of mycelium (approximately 10 mm in diameter) was generated from the original 5-mm-diameter agar plug.…”
Section: Methodsmentioning
confidence: 99%
“…The internal transcribed spacer (ITS), the intron 2 of the glyceraldehyde 3-phosphate dehydrogenase (GAPDH), part of the actin (ACT) and beta-tubulin 2 (TUB2) were amplified with the primer pairs ITS-5 / ITS-4 (White et al 1990), GDF1 / GDR1 (Guerber et al 2003), ACT-512F / ACT-783R (Carbone and Kohn 1999) and TUB2Fd / TUB4Rd (Aveskamp et al 2009), respectively, according to the protocol described by Damm et al (2012). The amplicons obtained were sent to MACROGEN Korea for sequencing in both directions with the primers mentioned before.…”
Section: Molecular Analysesmentioning
confidence: 99%